Primary succession of lichen and bryophyte communities following glacial recession on Signy Island, South Orkney Islands, Maritime Antarctic - Favero Longo S.; Worland M.R.; Convey P.; Smith R.I.L.; Piervittori R.; GUGLIELMIN, MAURO; CANNONE, NICOLETTA (Antarctic Science, 2012)
A directional primary succession with moderate species replacement was quantitatively characterized on Signy Island in zones of a glacial valley corresponding to their age since deglaciation. A continuous increase in diversity and abundance of lichens and bryophytes was observed between terrains deglaciated in the late 20th century, to areas where deglaciation followed the Little Ice Age, and others thought to be ice-free since soon after the Last Glacial Maximum. Classification (UPGMA) and ordination (principal co-ordinate analysis) of vegetation data identified three different stages of development: a) pioneer communities, which rapidly develop in a few decades, b) immature communities developing on three to four century old terrains, and c) a climax stage (Polytrichum strictum-Chorisodontium aciphyllum community) developing on the oldest terrains, but only where local-scale environmental features are more favourable. Multivariate analysis including environmental parameters (canonical correspondence analysis) indicated terrain age as being the dominant controlling factor, with other environmental factors also exhibiting significant conditional effects (duration of snow cover, surface stoniness). These findings not only quantitatively verify reports of the rapid colonization of Maritime Antarctic terrains following recent climate amelioration and associated decrease in glacial extent, but also show how local-scale environmental resistance may slow or even prevent vegetation succession from pioneer to more mature stages in future